Results of investigation of radionuclides content in drinking water in the observation zone of the Belarusian NPP - Zhukova, Olga M.; Nikalayenka, Alena M.; Sychyk, Siarhey I.; Kliaus, Viktoria V.; Drazdova, Alena V.; Matsko, Mikolaj G.; Tananka, Yauheni M. (Journal of the Belarusian State University. Ecology, 2021)
This article presents the results of studies of the content of natural (228Ra, 226Ra, 232Th, 40K, 210Po, 210Pb, 238U) and technogenic (137Cs, 90Sr) radionuclides in drinking water from centralized (wells) and decentralized (wells) water supplysources in the observation area of the Belarusian NPP, performed from 2016 to 2020 within the framework of radiation and hygienic monitoring at the stage of construction of the Belarusian NPP.
Keywords: radionuclides; drinking water; Belarusian NPP; observation area; radiation and hygienic monitoring